Professional practice in the hospital context: nurses' view on the contributions of Dorothea Orem's conceptions - Olga Maria Pimenta Lopes Ribeiro; Letícia de Lima Trindade; João Miguel Almeida Ventura Silva; Ana da Conceição Alves Faria (Universidade Federal de Santa Maria, 2021)
Objective: to analyze the concordance of nurses about the contributions of Dorothea Orem's conceptions to professional practice in the hospital context. Method: a quantitative cross-sectional study conducted in 36 Portuguese hospitals, with the participation of 3451 nurses. Data was collected using a questionnaire between July 2015 and March 2016. For analysis, descriptive and analytical statistics were used. Results: it was confirmed that 75 to 85% of the participants considered that Orem's conceptions regarding the four meta-paradigmatic concepts are in concordance or totally in concordance with their practice. The Region of the country, the service, and the condition in which the profession is practiced were the variables that influenced the concordance with the conceptions. Conclusion: the conformity observed in the results regarding the concordance of the nurses with the meta-paradigmatic concepts reinforces the contribution of Orem's framework to support the practice and to guarantee the scientificity of the profession.